Report on the National Consultation on Education held in September, 1999 - Trinidad and Tobago. National Advisory Committee on Education (Ministry of Education, 2000)
This is the report of public consultations on proposals to decentralize the Ministry of Education in Trinidad and Tobago. The topics of discussion for the consultation were: 1) Local school boards, 2) Restructuring and decentralization of the Ministry of Education, 3) Delinking and unification of the teaching service, and 4) Amendments to the Education Act.
Keywords: Local school boards